Protruded retinal layers within the optic nerve head neuroretinal rim. Issue 4 (20th July 2018) - Torres, Lucas A.; Vianna, Jayme R.; Jarrar, Faisal; Sharpe, Glen P.; Araie, Makoto; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Hangai, Masanori; Iwase, Aiko; Liebmann, Jeffrey M.; Mardin, Christian Y.; et al.
Abstract: Purpose: To determine the frequency with which retinal tissues other than the nerve fibre layer, hereafter referred to as protruded retinal layers (PRL), are a component of optical coherence tomography (OCT) neuroretinal rim measurements. Methods: Ninety healthy (30 White, Black and Japanese, respectively) subjects were included in the study. A radial scan pattern (24 B‐scans centred on Bruch's membrane opening [BMO]) was used. For each of the 48 minimum rim width (MRW) measurement points, we determined whether PRL were present, absent or indeterminate. When present, the proportion of PRL within the MRW was quantified. Results: Protruded retinal layers were present in 503 (11.6%), absent in 3805 (88.1%) and indeterminate in 12 (0.3%) measurement points. Overall, 69 (76.6%) subjects had ≥1 points with PRL, with White subjects having the highest frequency and Japanese the lowest (29 [97%] and 18 [60%], respectively; p   <   0.01). PRL were present in one‐third of points in the temporal sector, but ≤5% in other sectors. When present, the median PRL thickness was 53.0 (interquartile range [IQR]: 33.0 to 78.5) μ m, representing 20.6 (IQR: 13.0 to 28.5)% of MRW. Globally, the median PRL thickness comprised 1.3 (IQR: 0.2 to 3.5)% of the MRW; however, in the temporal sector, it exceeded 30% of MRW in some subjects. Conclusions: Protruded retinal layers are a component of MRW measurements in most normal subjects, occurring in almost 12% of all measurement points analysed. There were racial variations in the presence of PRL and a significantly higher frequency of PRL in the temporal sector.